Perfusion index in the preterm infant immediately after birth. Issue 8 (August 2015) - Hawkes, G.A.; O'Toole, J.M.; Kenosi, M.; Ryan, C.A.; Dempsey, E.M.
Abstract Aim To evaluate PI in preterm infants during the first 10 min of life. Design/methods An observational study was conducted in the delivery room on preterm infants (less than 32 week gestation). PI values were obtained from a pre ductal saturation probe placed on the right wrist. Analysis was performed on the first 10 min of data to investigate the correlation of PI with gestational age, heart rate, blood pressure, and lactate values. Results 33 infants with a median gestational age of 29 wks (IQR, 26–30 wks) and median birth weight of 1205 g (IQR, 925–1520 g) were included for analysis. The overall median PI value for the first 10 min was 1.3 (IQR, 0.86–1.68). There was no significant correlation found between delivery room PI and gestational age(r = 0.28, 95% CI: − 0.09, 0.59), lactate levels (r = − 0.25, 95% CI: − 0.62, 0.18) and blood pressure values (r = − 0.18, 95% CI: − 0.46, 0.20). An average correlation value of r = − 0.417 (95% CI: − 0.531, − 0.253) was found between PI and heart rate values. There was no statistical difference between the median of the median PI value over the first 5 min of life compared to the second 5 min (p = 0.22). Variability, as quantified by the IQR, was higher in the first 5 min compared to the second 5 min: median of 0.5(IQR, 0.27, 0.92) vs 0.2(IQR, 0.10, 0.30) (p < 0.00). Conclusions Delivery room PI values are easily obtained, however, have significant variability over the first 5 min of life and may add little to delivery room assessment.